Fetuin-A regulates adipose tissue macrophage content and activation in insulin resistant mice through MCP-1 and iNOS: involvement of IFNγ-JAK2-STAT1 pathway. Issue 22 (26th November 2021) - Chattopadhyay, Dipanjan; Das, Snehasis; Guria, Suktara; Basu, Soumyadeep; Mukherjee, Sutapa
Abstract : In the context of obesity-induced adipose tissue (AT) inflammation, migration of macrophages and their polarization from predominantly anti-inflammatory to proinflammatory subtype is considered a pivotal event in the loss of adipose insulin sensitivity. Two major chemoattractants, monocyte chemoattractant protein-1 (MCP-1) and Fetuin-A (FetA), have been reported to stimulate macrophage migration into inflamed AT instigating inflammation. Moreover, FetA could notably modulate macrophage polarization, yet the mechanism(s) is unknown. The present study was undertaken to elucidate the mechanistic pathway involved in the actions of FetA and MCP-1 in obese AT. We found that FetA knockdown in high fat diet (HFD) fed mice could significantly subdue the augmented MCP-1 expression and reduce adipose tissue macrophage (ATM) content thereby indicating that MCP-1 is being regulated by FetA. Additionally, knockdown of FetA in HFD mice impeded the expression of inducible nitric oxide synthase (iNOS) reverting macrophage activation from mostly proinflammatory to anti-inflammatory state. It was observed that the stimulating effect of FetA on MCP-1 and iNOS was mediated through interferon γ (IFNγ) induced activation of JAK2-STAT1-NOX4 pathway. Furthermore, we detected that the enhanced IFNγ expression was accounted by the stimulatory effect of FetA upon the activities of both cJun and JNK. Taken together, our findings revealed that obesity-induced FetA acts as a master upstream regulator of AT inflammation by regulating MCP-1 and iNOS expression through JNK-cJun-IFNγ-JAK2-STAT1 signaling pathway. This study opened a new horizon in understanding the regulation of ATM content and activation in conditions of obesity-induced insulin resistance.